PROBLEMS AND SOLUTIONS OF USING ARTIFICIAL INTELLIGENCE IN THE EDUCATIONAL PROCESS (Universal International Scientific Journal, 2026)
The current aspects of the use of artificial intelligence technologies in the educational process, existing problems and ways to overcome them are analyzed. In particular, the importance of artificial intelligence in individualizing the educational process, improving the quality of education, and supporting the activities of teachers and students is highlighted. At the same time, methodological, technical, ethical and organizational problems encountered in the implementation of these technologies are considered. In particular, special attention is paid to issues such as digital inequality, data security, violation of academic integrity, and insufficient digital competence of teachers. As a result of the study, the need to train teachers, develop digital infrastructure, improve legal and regulatory frameworks, and maintain the priority of the human factor in the educational process is substantiated.
Keywords: artificial intelligence, educational process, digital education, innovative technologies, educational quality, academic integrity, digital competence, information security, individualized education, pedagogical approach.